Probing galaxy formation with high energy gamma-rays - Primack, J; Somerville, R; Bullock, J; Devriendt, J (AIP Publishing, 2001)
We discuss how measurements of the absorption of $γ$-rays from GeV to TeV energies via pair production on the extragalactic background light (EBL) can probe important issues in galaxy formation. We use semi-analytic models (SAMs) of galaxy formation, set within the hierarchical structure formation scenario, to obtain predictions of the EBL for 0.1-1000$μ$m. SAMs incorporate simplified physical treatments of the key processes of galaxy formation --- including gravitational collapse and merging of dark matter halos, gas cooling and dissipation, star formation, supernova feedback and metal production --- and have been shown to reproduce key observations at low and high redshift. Here we also introduce improved modelling of the spectral energy distributions in the mid-to-far-IR arising from emission by dust grains. Assuming a flat \lcdm cosmology with $Ω_m=0.3$ and Hubble parameter $h=0.65$, we investigate the consequences of variations in input assumptions such as the stellar initial mass function (IMF) and the efficiency of converting cold gas into stars. We conclude that observational studies of the absorption of $γ$-rays with energies from 10s of Gev to 10s of TeV will help to determine the EBL, and also help to explain its origin by constraining some of the most uncertain features of galaxy formation theory, including the IMF, the history of star formation, and the reprocessing of light by dust.